EKSISTENSI HUTAN WONOSADI: ANTARA MITOS DAN KEARIFAN LINGKUNGAN - Sartini Sartini (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2010)
AbstractEcological perspective is a significant issue nowadays because there are many kinds of disaster around us stimulated by ecological disturbance. Actually, we have traditional knowledge and wisdoms to sustain the nature and protect it. This point of view is usually melted in mythological beliefs and traditional rituals. This is also showed by people around Wonosadi forest.The mythological belief connects to the existence of Wonosadi forest. This belief supports an ecological wisdom which functions in the forest sustainability. This wisdom is implied by a view of Wonosadi’s people about relation between man, nature, and God. Human should thank to God by praying and serving a good conduct to nature. All of them are one system that connects one and each other. This view must be a combination between spiritualistic and rationalistic understanding. This thought shows an organicholistic view.Keywords: myth, belief, mythology, spiritual, ecology, ecologicalwisdom, rational.